Investigation on Performance Evaluation Indices for Quick- freezers - 吕静; 郇中杰; 何绍书; 毛力 (Zhileng xuebao)
The performance evaluation indices of quick-freezers were discussed. The analysis shows that there is a limitation in evaluating the performance for quick-freezing installation using COP, frozen velocity, and the energy consuming of frozen-food per mass quality. Based on the analysis of the air flow organization and the total performance in the freezer, three new items namely energy utilization efficiency, efficiency of airflow organization, and uniform coefficient of air flow organization were proposed to compare the performance for quick-freezers. Moreover, the performance indices were applied to analyze the performance and to evaluate and compare different quick-freezers. The results indicate that the improvement of the airflow organization is critical to the higher performance and the problem with the quick-freezers can be detected with these new indices.